2023
DOI: 10.3389/fonc.2023.1098459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the preoperative prognostic nutritional index on the long-term prognosis in patients with borderline resectable pancreatic cancer after pancreaticoduodenectomy

Abstract: BackgroundThe preoperative prognostic nutritional index (PNI) is an indicator of systemic immune-nutritional condition and is a well-known prognostic biomarker in cancer patients. This study aims to reflect the correlation between the preoperative PNI and prognosis in patients with borderline resectable pancreatic cancer (BRPC) after pancreaticoduodenectomy (PD).MethodsMedical records of patients with BRPC after PD between Jan 2011 and Dec 2021 in our hospital were retrospectively analyzed. The preoperative PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, we investigated the predictive value of 12 clinicopathologic variables (gender, age, tumor size, degree of differentiation, tumor location, TNM stage, lymph node metastasis, vascular cancer thrombus, peripheral nerve invasion, CEA, CA199, CA125) for resectable pancreatic ductal adenocarcinoma, and many attempts have been made to determine the prognostic factors of PDAC in addition to several well-known factors such as TNM stage and carbohydrate antigen 19 − 9 (CA19-9) [ 25 ],In several previous studies, LN status and degree of tumor differentiation were identified as prognostic factors for resectable PDAC [ 26 – 28 ],and these findings are consistent with the results of this study, which suggest that LN status and degree of differentiation are independent prognostic factors in patients with PDAC. In addition, studies have shown that neoadjuvant chemotherapy can inhibit tumor progression and effectively prolong postoperative survival [ 29 ].however, there is still a lack of uniform criteria for selecting patients who are candidates for neoadjuvant therapy. In our study, we did not include these patients in order to rule out the effect of preoperative neoadjuvant chemotherapy on our outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the predictive value of 12 clinicopathologic variables (gender, age, tumor size, degree of differentiation, tumor location, TNM stage, lymph node metastasis, vascular cancer thrombus, peripheral nerve invasion, CEA, CA199, CA125) for resectable pancreatic ductal adenocarcinoma, and many attempts have been made to determine the prognostic factors of PDAC in addition to several well-known factors such as TNM stage and carbohydrate antigen 19 − 9 (CA19-9) [ 25 ],In several previous studies, LN status and degree of tumor differentiation were identified as prognostic factors for resectable PDAC [ 26 – 28 ],and these findings are consistent with the results of this study, which suggest that LN status and degree of differentiation are independent prognostic factors in patients with PDAC. In addition, studies have shown that neoadjuvant chemotherapy can inhibit tumor progression and effectively prolong postoperative survival [ 29 ].however, there is still a lack of uniform criteria for selecting patients who are candidates for neoadjuvant therapy. In our study, we did not include these patients in order to rule out the effect of preoperative neoadjuvant chemotherapy on our outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a common diagnosis among cancer patients and has a considerable effect on the prognosis [ 29 ].Progressive malnutrition is strongly associated with the development of cachexia, especially in patients with pancreatic and gastric cancers [ 30 ].Epidemiological studies on the relationship between serum albumin levels and survival in cancer patients have found that decreased serum albumin levels are associated with reduced survival [ 31 ].The relationship between pretreatment albumin levels and prognosis for head and neck cancer [ 32 ],kidney cancer [ 33 ], cardia adenocarcinoma [ 34 ], and ovarian cancer [ 35 ] has been reported. Inflammation is known to play a key role in the initiation, progression, and prognosis of tumors, and lymphocytes can not only effectively recognize tumor cells, but also be stimulated by tumor antigens to transform into sensitized lymphocytes to attack tumor lesions, thereby producing antitumor activity, inhibiting angiogenesis, and improving tumor prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%